JIHAD FIQH PERSPECTIVE: AN ANALYSIS OF FATHUL MU’IN BY ZAINUDDIN AL-MALIBARI - Khoirul Fatih, Moh; Fatih, Moh. Khoirul; Thiyas Tono Taufiq; Moh. Shofi Zuhri; Ach. Ilham Zubairi (MADINAH, 2025)
Muslims today face quite serious internal problems, especially the emergence of exclusive religious movements that tend to construct fellow Muslims as “the other” simply because of differences in religious views. On the other hand, there are also groups that commit acts of violence in the name of God and religion, as if religion provides moral legitimacy for aggressive actions against other groups. In this situation, the theme of jihad becomes increasingly important to study, not only because it continues to be an academic debate, but also because the concept is often misunderstood and misused in the context of contemporary religious society. This study examines the concept of jihad in Zainuddin al-Malibari's Fatḥ al-Mu‘īn by highlighting its four levels: (1) inviting people to believe in Allah rationally and argumentatively, (2) striving to fulfill sharia obligations, (3) waging defensive warfare when Muslims are disturbed, and (4) providing protection for all members of society, both Muslim and non-Muslim. The concept of jihad in this text is positioned as fardhu kifayah, which can change to fardhu 'ain according to the demands of the context. The novelty of this research lies in its attempt to reconstruct al-Malibari's paradigm of jihad as a normative foundation for peace building in a pluralistic religious society. This research shows that jihad is not only related to militancy or self-defense, but also encompasses ethical, social, and protective dimensions that are often overlooked in contemporary discourse. The findings of this study confirm that the framework of jihad in Fatḥ al-Mu‘īn has strong relevance for strengthening interfaith harmony, overcoming tendencies toward exclusivism, and promoting peaceful coexistence in the context of today's diversity